Targeted next-generation sequencing of cancer genes in poorly differentiated thyroid cancer. Issue 1 (January 2018) - Gerber, Tiemo S; Schad, Arno; Hartmann, Nils; Springer, Erik; Zechner, Ulrich; Musholt, Thomas J
Abstract : Poorly differentiated thyroid carcinoma (PDTC) is a rare malignancy with higher mortality than well-differentiated thyroid carcinoma. The histological diagnosis can be difficult as well as the therapy. Improved diagnosis and new targeted therapies require knowledge of DNA sequence changes in cancer-relevant genes. The TruSeq Amplicon Cancer Panel was used to screen cancer genomes from 25 PDTC patients for somatic single-nucleotide variants in 48 genes known to represent mutational hotspots. A total of 4490 variants were found in 23 tissue samples of PDTC. Ninety-eight percent (4392) of these variants did not meet the inclusion criteria, while 98 potentially pathogenic or pathogenic variants remained after filtering. These variants were distributed over 33 genes and were all present in a heterozygous state. Five tissue samples harboured not a single variant. Predominantly, variants in P53 (43% of tissue samples) were identified, while less frequently, variants in APC, ERBB4, FLT3, KIT, SMAD4 and BRAF (each in 17% of tissue samples) as well as ATM, EGFR and FBXW7 (each in 13% of tissue samples) were observed. This study identified new potential genetic targets for further research in PDTC. Of particular interest are four observed ERBB4 (alias HER4 ) variants, which have not been connected to this type of thyroid carcinoma so far. In addition, APC and SMAD4 mutations have not been reported in this subtype of cancer either. In contrast to other reports, we did not find CTNNB1 variants.